Reconstruction of Breach of Performance & Unlawful Acts in Book III of Civil Law (Islamic Legal Analysis) - Ismanto, Dedi; Albani, Muhammad Syukri; Adly, M. Amar (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study examines the conceptual differences between default and unlawful acts in Book III of the Civil Code and reconstructs both concepts in the context of Indonesian civil law. In addition, this study analyzes the perspective of Islamic law on the reconstruction carried out. The method used is normative legal research with a statute approach and a conceptual approach. The results of the study indicate that default and unlawful acts have fundamental differences, where default arises due to a violation of an agreement, while unlawful acts are based on a violation of rights or legal norms. Book III of the Civil Code has provided a clear legal framework related to these two concepts, although in practice it still needs to be strengthened in implementation and adaptation to social developments. The reconstruction carried out in this study confirms that Indonesian civil law continues to develop in accordance with the dynamics of society. From an Islamic legal perspective, the principles of justice, individual responsibility, and good faith in transactions have strong relevance in understanding default and unlawful acts. This study contributes to the development of civil law theory and practice in Indonesia and enriches the study of Islamic law in the context of modern civil law.